Analisis Cyber Public Relations Dinas Pertamanan dan Hutan Kota DKI Jakarta @tamahutandki - Firdaus, Rivan; Meliala, Robbikal Muntaha; Susanto, Teguh Tri (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The development of communication technology has driven a transformation in government public relations strategies through the use of social media. The Jakarta Parks and Urban Forest Service (Distamhut DKI Jakarta) utilizes Instagram @tamanhutandki to deliver public information, including the “Gerakan Rabu Menoping” (Wednesday Pruning Movement) as a flagship program for tree-fall mitigation. This study aims to analyze the practice of Cyber Public Relations by Distamhut DKI Jakarta in managing this content. The research employed a qualitative method with data collected through in-depth interviews, observation, documentation, and literature review. Using Rulli Nasrullah’s Cyber Media Analysis (AMS), findings reveal that @tamanhutandki serves as an institutional representation space, with media documents presented through repetitive visual narratives, informative captions, and consistent hashtags. Media objects indicate predominantly passive audience engagement, while public experience is shaped through repeated exposure, fostering awareness of tree-fall risks. The results highlight that Instagram functions as a tool for public transparency, visual communication, and digital relationship-building between government and society. However, content distribution requires further optimization to expand outreach and engagement.